A new dawn for MENA firms: service trade liberalization for more competitive exports. Issue 1 (2nd January 2020) - Karam, Fida; Zaki, Chahir
ABSTRACT: While micro-level empirical evidence has emerged to highlight the positive effect of services deregulation on the productivity and exports of manufacturing firms in developing countries, the MENA region has been neglected in the literature. The current paper fills the gap by exploring the effect of service protection on the extensive and intensive trade margins of manufacturing and services firms in selected MENA countries for 2013. The service protection variable is constructed using two different measures: the service trade restrictiveness index and the tariff equivalent of services, weighted by the input-output technical coefficient of service sectors. Our results show that service protection is a fixed export cost, exerting a negative and significant effect on the extensive margin, without having a significant effect on the intensive margin of the firm. We also find that the burden of service barriers falls on small firms that struggle to enter international markets, and on firms operating in high value-added sectors such as 'motor vehicles'.